Особенности точных решений задачи об электроне в квантовом поле плоской волны; Известия вузов. Физика; Т. 20, № 3 - Багров В. Г. Владислав Гаврилович; Гитман Д. М. Дмитрий Максимович; Задорожный В. Н. Валерий Николаевич; Лавров П. М. Петр Михайлович (1977, 1977)
Заглавие с экрана